2013
DOI: 10.2337/dc13-0355
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of the Booster-Enhanced READY-Girls Preconception Counseling Program on Intentions and Behaviors for Family Planning in Teens With Diabetes

Abstract: OBJECTIVETo examine 12-month effects of a booster-enhanced preconception counseling (PC) program (READY-Girls) on family planning for teen girls with type 1 and type 2 diabetes.RESEARCH DESIGN AND METHODSParticipants 13–19 years of age (n = 109) were randomized to a standard care control group (CG) or intervention group (IG) that received PC over three consecutive clinic visits. Prepost data were collected at baseline, 3- and 6-month booster sessions, and a 12-month follow-up visit.RESULTSMean age was 15.8 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 10 publications
(22 reference statements)
1
90
0
1
Order By: Relevance
“…These questionnaires were given at baseline, pre and post at each intervention session (3 months and 6 months), and at the 12-month follow-up. The methods and sample for the RCT have been described in detail elsewhere [14]. Prior to randomization, all participants completed both open-ended items (understanding) and a close-ended measure (knowledge) about reproductive health concerning diabetes and pregnancy, diabetes and contraception, and PC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These questionnaires were given at baseline, pre and post at each intervention session (3 months and 6 months), and at the 12-month follow-up. The methods and sample for the RCT have been described in detail elsewhere [14]. Prior to randomization, all participants completed both open-ended items (understanding) and a close-ended measure (knowledge) about reproductive health concerning diabetes and pregnancy, diabetes and contraception, and PC.…”
Section: Methodsmentioning
confidence: 99%
“…Several of the successful components of teen pregnancy prevention programs (e.g., abstinence as one method of family planning/pregnancy prevention, delay of sexual initiation, improving communication, and skills building) [9,10] were also integrated into the READY-Girls program that was formatted as a multi-media awareness educational program [11]. The efficacy of READY-Girls has been validated through several randomized control trials (RCT) [12,13,14], and it was shown to be cost-effective [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…READY-Girls is a validated developmentally appropriate evidence-based educational PC intervention for adolescent girls starting at puberty [8][9][10]. Three randomized controlled trials (RCT) at multiple diabetes clinic sites using the READY-Girls intervention have been conducted (1999,2002, and 2005) on teens 13-20 years of age and results have been previously reported [11][12][13]. Along-term follow-up survey study was later conducted online with past READY-Girls participants regarding PC and pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%